2016
DOI: 10.12972/kjhst.20160081
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hypo- and Hypertetraploid Seedlings from Open-, Self-, and Cross-Pollinated Hypo- and Hypertetraploid Grape

Young-Sik Park,
Jae-Yun Heo,
Sung-Min Park

Abstract: Seedless grape (Vitis spp.) cultivars with large berries can be developed from hypo-and hypertetraploid seedlings. The low occurrence of hypo-and hypertetraploid seedlings, however, has impeded the breeding of new hypo-and hypertetraploid grape varieties. In order to establish hypoand hypertetraploid seedlings, we examined the chromosome numbers in seedlings of self-, open-, and cross-pollinated hypotetraploid 'Takao' and hypertetraploid 'RB9127K' grape. Three of the five seedlings (60%) from 'Takao' were aneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Of them, only 12 seeds germinated. The triploidy status of these individuals was confirmed by counting the chromosome number as described by Park et al (2016). 'Black Star', initially named 'GWT-80', which was identified as a triploid selection with superior growth characteristics during its early growth stages, was multiplied for evaluation of its vine performance and fruit quality in the y Ten clusters from gibberellic acid-treated (100 ppm) vines were sampled randomly from five vines at the optimal harvest period for calculation.…”
Section: Originmentioning
confidence: 99%
“…Of them, only 12 seeds germinated. The triploidy status of these individuals was confirmed by counting the chromosome number as described by Park et al (2016). 'Black Star', initially named 'GWT-80', which was identified as a triploid selection with superior growth characteristics during its early growth stages, was multiplied for evaluation of its vine performance and fruit quality in the y Ten clusters from gibberellic acid-treated (100 ppm) vines were sampled randomly from five vines at the optimal harvest period for calculation.…”
Section: Originmentioning
confidence: 99%
“…It was found that cross between hypotetraploid and tetraploid grapes generates hypotetraploids more easily compared to previously used breeding methods. However, low seed germination caused by abortive embryos after cross pollination has remained a problem that hinders the breeding of hypotetraploid grape cultivars (Park et al, 2016). In vitro embryo rescue technique has been successfully applied to generate hybrid seedlings that can hardly be obtained by artificial cross combination of grape cultivars such as stenospermic × stenospermic or tetraploid × diploid grapes (Liu et al, 2016;Jiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many efforts have been made to breed new grape cultivars in Korea, and various grape cultivars are being introduced to farmers (Park et al, 2016;Heo and Park, 2017;Roh et al, 2018;Kim et al, 2020;Park et al, 2022). Among them, 'Red Dream', which is a triploid grape registered in 2016, has the advantage of being able to produce large seedless fruits with just one-time treatment of PGR at the full bloom stage (Park et al, 2022).…”
mentioning
confidence: 99%